CHA2DS2VASc score and adverse outcomes in middle-aged individuals without atrial fibrillation. (December 2019) - Renda, Giulia; Ricci, Fabrizio; Patti, Giuseppe; Aung, Nay; Petersen, Steffen E; Gallina, Sabina; Hamrefors, Viktor; Melander, Olle; Sutton, Richard; Engstrom, Gunnar; Caterina, Raffaele De; Fedorowski, Artur
Aims: The CHA2 DS2 VASc score is used to evaluate the risk of thromboembolic events in patients with non-valvular atrial fibrillation. We assessed the prognostic yield of CHA2 DS2 VASc for new-onset atrial fibrillation, cardiovascular morbidity and mortality in a non-atrial fibrillation population. Methods: We analysed a population-based cohort of 22, 179 middle-aged individuals with ( n  = 3542) and without ( n  = 18, 367) a history of atrial fibrillation; we grouped the population into five CHA2 DS2 VASc strata (0–1–2–3–≥4), and compared the risk of major adverse cerebro-cardiovascular events and mortality. Furthermore, we analysed the annual incidence of atrial fibrillation across different CHA2 DS2 VASc strata. Results: Over a median follow-up of 15 years, 1572 patients (6.9%) had ischaemic strokes, 2162 (9.5%) coronary events and 5899 (26%) died. The cumulative incidence of ischaemic stroke in CHA2 DS2 VASc ≥ 4 subjects without atrial fibrillation was similar to patients with atrial fibrillation and CHA2 DS2 VASc 2, with a 10-year crude incidence rate of 0.91 (95% confidence interval (CI) 0.68–1.19) and 1.13 (95% CI 0.93–1.36) ischaemic strokes per 100 patient-years, respectively. CHA2 DS2 VASc in a non-atrial fibrillation population showed higher predictive accuracy for ischaemic stroke compared with an atrial fibrillation population (area under the curve 0.60 vs. 0.56; P  = 0.001). In multivariable Cox regression analysis, CHA2 DS2 VASc ≥ 2 was an independent predictor of all-cause death (adjusted hazard ratio (aHR) 2.58; 95% CI 2.42–2.76), cardiovascular death (aHR 3.40; 95% CI 2.98–3.89), ischaemic stroke (aHR 2.20; 95% CI 1.92–2.53) and coronary events (aHR 1.83; 95% CI 1.63–2.04). The cumulative incidence of atrial fibrillation was greater with increasing CHA2 DS2 VASc strata, with an absolute annual incidence of more than 2% per year if CHA2 DS2 VASc ≥ 4. Conclusion: The CHA2 DS2 VASc score is a sensitive tool for predicting new-onset atrial fibrillation and adverse outcomes in subjects both with and without atrial fibrillation.